Gestión del talento humano en el Gobierno Autónomo Descentralizado Municipal del Cantón Montalvo periodo 2022 - 2023. - Martínez Altamirano, Fanny Stefania (2023)
This study focuses on analyzing human talent management in the Municipal Decentralized Autonomous Government of Montalvo Canton, using the "Root Cause" method, which allows for the identification of the origins of the challenges currently facing the institution due to an excess of personnel. This excess affects the execution of its functions and the quality of services provided to the community. In addition to examining human talent management processes such as personnel recruitment planning through an interview with the Head of Human Resources of the institution. Likewise, this study has conducted surveys targeting a sample of the active population of the canton, with the purpose of assessing the impact on the efficiency and quality of public services. The results reveal dissatisfaction and concern about the imbalance in task allocation relative to the perceived quality of services. The obtained results highlight the importance of monitoring and evaluating various resource management processes within the institution, conducting a comprehensive review of hiring policies, and implementing employee training programs. All of these efforts aim to optimize human talent management specifically to achieve an appropriate allocation of responsibilities, enhance productivity, and meet community expectations.